Effectiveness of Training on the Ability of Voluntary Corps Students to Provide First Aid for Syncope - Nurjannah, Misbah; Sari, Putri Agustina Nila; Widyastuti, Dwi (Universitas Ibn Khaldun Bogor, 2025)
Background: Temporary loss of consciousness that happens suddenly is called syncope. Dehydration, exhaustion, hypoglycemia, and heat stroke can all lead to syncope by reducing blood and oxygen flow to the brain. Paleness, dizziness, cold sweats, and blurred vision are the symptoms of this illness. Objective: The purpose of this study is to ascertain how training affects Korps Sukarela students' first aid for syncope knowledge and abilities. Methods: This study employed with one group pretest-posttest methodology. Through the use of random sampling, the study's sample was chosen, resulting in 72 responses. Before and after training, respondents completed pretest and posttest questionnaires, and researchers evaluated the information on the observation sheets. SPSS was used for both univariate and bivariate analysis of the research findings. Result: The study's findings demonstrated that training had an impact on KSR students' syncope first aid knowledge and abilities. KSR students' knowledge and abilities have increased both before and after instruction. Conclusion: There is a significant relationship between training and increasing the knowledge and skills of KSR students in first aid for syncope.